Nano lithium iron phosphate material, positive electrode sheet and secondary battery
By using a combination of nano lithium iron phosphate particles, covalent organic frames and single-wall carbon nanotubes in battery materials, the slurry gel problem caused by agglomeration of nano lithium iron phosphate particles is solved, and high power performance is maintained under low temperature conditions. .
Patent Information
- Application Number
- CN202111361139.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-11-17
AI Technical Summary
Nano lithium iron phosphate particles are prone to agglomeration during standstill, resulting in slurry gels, affecting battery performance, and the prior art is difficult to maintain high power performance under low temperature conditions of the battery.
Using materials containing nano lithium iron phosphate particles, covalent organic frames and single-wall carbon nanotubes, nano lithium iron phosphate particles are fixed through the pores of the covalent organic frame, and the conductivity of the material is improved through the single-wall carbon nanotubes.
It effectively avoids the agglomeration of nano-lithium iron phosphate particles, prevents slurry gel, maintains the high power performance of the battery under low temperature conditions, and improves the safety of the battery.
Smart Images

Figure CN115832300B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a nano lithium iron phosphate material, a positive electrode slurry, a positive electrode sheet, a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] Secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. Lithium iron phosphate (LFP for short) is an important secondary battery material with a chemical formula of LiFePO4, which can be used as a positive electrode active material for secondary batteries. Lithium iron phosphate can be formed into a slurry together with other ingredients and coated on the positive electrode current collector to form a positive electrode sheet.
[0003] Lithium iron phosphate is usually used in the form of nano-powder. Nano-lithium iron phosphate is very easy to agglomerate due to its relatively small particle size, which makes the slurry easy to gel during the static process, affecting its use.
[0004] The existing technology generally adopts two solutions to solve the gel problem of nano lithium iron phosphate. One is to add a dispersant during the slurry stirring, but this technology has limited effect in alleviating the gel, and the slurry will still produce gel when it is left standing for a long time; in addition, since the dispersant is not conductive, it is easy to increase the direct current resistance (DCR) of the battery, which is not conducive to improving the power performance of the battery. Another solution is to stir the slurry slowly in the stirring tank, let it stand and gel, and then stir it back and adjust the viscosity. However, this solution cannot achieve continuous stirring in the slurry delivery pipeline, so it cannot solve the problem of gel in the delivery pipeline; in addition, back stirring will increase the amount of organic solvent used, increase costs, and reduce production efficiency.
[0005] Therefore, the art needs to develop a new nano lithium iron phosphate material to solve the problem of slurry gelation while maintaining the low-temperature power performance of the battery without deterioration. Summary of the invention
[0006] The present application is made in view of the above-mentioned problems, and its purpose is to provide a nano lithium iron phosphate material, which, as a positive electrode active material of a secondary battery, can effectively prevent the agglomeration of nano lithium iron phosphate particles during the standing process, prevent the slurry from generating gel during the standing process, and at the same time maintain the low-temperature power performance of the battery without deterioration.
[0007] In order to achieve the above-mentioned objectives, the present application provides a nano lithium iron phosphate material, a positive electrode slurry and a positive electrode sheet, as well as a method for preparing the nano lithium iron phosphate material, the positive electrode slurry and the positive electrode sheet, and also provides a secondary battery, a battery module, a battery pack and an electrical device.
[0008] The first aspect of the present application provides a nano lithium iron phosphate material, which comprises nano lithium iron phosphate particles, a covalent organic framework and single-walled carbon nanotubes; the nano lithium iron phosphate particles are located in the pores of the covalent organic framework; the single-walled carbon nanotube material is distributed on the skeleton of the covalent organic framework, or filled in the gap between the covalent organic framework and the nano lithium iron phosphate particles.
[0009] In some embodiments, the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1.1.
[0010] In some embodiments, the particle size of the nano lithium iron phosphate particles is less than or equal to 100 nm.
[0011] In some embodiments, the single-walled carbon nanotube has a diameter of 0.7 nm to 1 nm, a length of 10 μm to 30 μm, and / or a specific surface area of 1000 m 2 / g~2000m 2 / g.
[0012] In some embodiments, the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF.
[0013] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93% to 96%: 0.6% to 2%: 0.1% to 1% by mass.
[0014] The second aspect of the present application provides a method for preparing a nano lithium iron phosphate material, comprising the following steps:
[0015] (1) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles;
[0016] (2) adding single-walled carbon nanotubes to the material of step (1) and stirring and mixing to obtain the nano lithium iron phosphate material.
[0017] In some embodiments, the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.1.
[0018] In some embodiments, the particle size of the nano lithium iron phosphate particles is less than or equal to 100 nm.
[0019] In some embodiments, the single-walled carbon nanotube has a diameter of 0.7 nm to 1 nm, a length of 10 μm to 30 μm, and / or a specific surface area of 1000 m 2 / g~2000m 2 / g.
[0020] In some embodiments, the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF.
[0021] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93-96: 0.6-2: 0.1-1 by mass.
[0022] In some embodiments, the method is carried out in a stirred tank, and in step (1), the rotational speed of the stirred tank is 20 rpm to 30 rpm, and the rotational speed is 700 rpm to 900 rpm; in step (2), the rotational speed of the stirred tank is 20 rpm to 30 rpm, and the rotational speed is 1000 rpm to 1500 rpm.
[0023] The third aspect of the present application provides a positive electrode slurry, comprising the nano lithium iron phosphate material of the first aspect of the present application, or the nano lithium iron phosphate material prepared by the method of the second aspect of the present application. Optionally, the positive electrode slurry further comprises one or more of a conductive agent, a binder and an organic solvent.
[0024] In some embodiments, the positive electrode slurry includes the nano lithium iron phosphate material, a conductive agent, a binder, and an organic solvent.
[0025] In some embodiments, the ratio of the mass of the binder to (the sum of the masses of the nano-lithium iron phosphate material, the conductive agent and the binder) is 1.5%:100% to 2.5%:100%, in terms of mass percentage.
[0026] In some embodiments, the ratio of the mass of the conductive agent to (the sum of the masses of the nano-lithium iron phosphate material, the conductive agent and the binder) is 2%:100% to 4%:100%, in terms of mass percentage.
[0027] In some embodiments, the ratio of the mass of the organic solvent to the mass of the positive electrode slurry is 40%:100% to 50%:100%, in terms of mass percentage.
[0028] In some embodiments, the mass ratio of (the sum of the mass of the nano-lithium iron phosphate material, the conductive agent and the binder): the mass ratio of the positive electrode slurry is 50%:100% to 60%:100%, in terms of mass percentage.
[0029] A fourth aspect of the present application provides a method for preparing a positive electrode slurry, comprising the following steps:
[0030] (i) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles;
[0031] (ii) adding single-walled carbon nanotubes, a binder, a conductive agent and an organic solvent to the material of step (i) and stirring and mixing.
[0032] In some embodiments, the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.1.
[0033] In some embodiments, the particle size of the nano lithium iron phosphate particles is less than or equal to 100 nm.
[0034] In some embodiments, the single-walled carbon nanotube has a diameter of 0.7 nm to 1 nm, a length of 10 μm to 30 μm, and / or a specific surface area of 1000 m 2 / g~2000m 2 / g.
[0035] In some embodiments, the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF.
[0036] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93-96: 0.6-2: 0.1-1 by mass.
[0037] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes: binder: conductive agent is 93-96: 0.6-2: 0.1-1: 1.5-2.5: 2-4 in mass fractions.
[0038] In some embodiments, the ratio of the mass of the organic solvent to the mass of the nano-lithium iron phosphate particles, the covalent organic framework, the single-walled carbon nanotubes, the conductive agent and the binder is 40:100 to 50:100, in parts by mass.
[0039] In some embodiments, the method comprises the following steps:
[0040] (1) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles;
[0041] (2) adding a binder and a conductive agent to the material of step (1) and stirring and mixing;
[0042] (3) adding an organic solvent to the material of step (2) and stirring and mixing;
[0043] (4) adding single-walled carbon nanotubes to the material in step (3) and stirring and mixing;
[0044] (5) Continuously stirring, adjusting the viscosity to 7000 Pa·s to 15000 Pa·s, and continuing to stir to obtain the positive electrode slurry.
[0045] In some embodiments, the method is carried out in a stirred tank, and in steps (1), (2), and (3), the rotational speed of the stirred tank is 20 rpm to 30 rpm, and the rotational speed is 700 rpm to 900 rpm; in step (4), the rotational speed of the stirred tank is 20 rpm to 30 rpm, and the rotational speed is 1000 rpm to 1500 rpm.
[0046] In some embodiments, step (5) includes: first continuously stirring at an orbital speed of 25 rpm to 30 rpm and a rotational speed of 500 rpm to 600 rpm, adjusting the viscosity within the range of 7000 Pa·s-15000 Pa·s by adding a solvent, and continuously slowly stirring at an orbital speed of 10 rpm to 20 rpm to obtain a positive electrode slurry containing nano lithium iron phosphate material.
[0047] The fifth aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer comprises the nano lithium iron phosphate material of the first aspect of the present application, or comprises the nano lithium iron phosphate material prepared by the method of the second aspect of the present application.
[0048] Optionally, the positive electrode film layer further comprises a conductive agent and a binder. In some embodiments, the binder accounts for 1.5% to 2.5% of the positive electrode film layer by mass, and in some embodiments, the conductive agent accounts for 2% to 4% of the positive electrode film layer.
[0049] The sixth aspect of the present application provides a method for preparing a positive electrode sheet, comprising the following steps: coating the positive electrode slurry of the third aspect of the present application or the positive electrode slurry prepared by the method of the fourth aspect of the present application on a positive electrode collector, and obtaining a positive electrode sheet after cold pressing, slitting and other processes.
[0050] The seventh aspect of the present application provides a secondary battery, comprising the nano lithium iron phosphate material of the first aspect of the present application, the nano lithium iron phosphate material produced by the method of the second aspect of the present application, the positive electrode plate of the fifth aspect of the present application, or the positive electrode plate produced by the method of the sixth aspect of the present application.
[0051] The eighth aspect of the present application provides a battery module, comprising the nano lithium iron phosphate material of the first aspect of the present application, the nano lithium iron phosphate material produced by the method of the second aspect of the present application, the positive electrode plate of the fifth aspect of the present application, or the positive electrode plate produced by the method of the sixth aspect of the present application, or the secondary battery of the seventh aspect of the present application.
[0052] The ninth aspect of the present application provides a battery pack, comprising the nano lithium iron phosphate material of the first aspect of the present application, the nano lithium iron phosphate material produced by the method of the second aspect of the present application, the positive electrode plate of the fifth aspect of the present application, or the positive electrode plate produced by the method of the sixth aspect of the present application, or the secondary battery of the seventh aspect of the present application, or the battery module of the eighth aspect of the present application.
[0053] The tenth aspect of the present application provides an electrical device, including the nano lithium iron phosphate material of the first aspect of the present application, the nano lithium iron phosphate material produced by the method of the second aspect of the present application, the positive electrode plate of the fifth aspect of the present application, or the positive electrode plate produced by the method of the sixth aspect of the present application, or the secondary battery of the seventh aspect of the present application, or the battery module of the eighth aspect of the present application, or the battery pack of the ninth aspect of the present application.
[0054] The nano-lithium iron phosphate material provided by the present application can be used as a positive electrode active material for a secondary battery, and can effectively prevent the nano-lithium iron phosphate particles from agglomerating during the static process, so that the electrode slurry does not agglomerate or gel after being static for 48 hours, while maintaining the low-temperature power performance of the battery without deterioration. Furthermore, the nano-lithium iron phosphate material of the present invention also improves the problem of central hole collapse that is prone to occur in cylindrical batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The structural formula of TFPPY-PYTTA COF is shown, and the synthetic route is exemplarily given.
[0056] Figure 2 It is a schematic structural diagram of the nano lithium iron phosphate material provided in this application.
[0057] Figure 3 Schematic diagram of a secondary battery with a square structure according to one embodiment of the present application.
[0058] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0059] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.
[0060] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0061] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0062] Figure 3-Figure 7 Description of the reference numerals in the figure: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly.
[0063] Figure 8 Schematic diagram of a secondary battery with a cylindrical structure according to one embodiment of the present application.
[0064] Fig. 9 yes Figure 8 The exploded view of a secondary battery according to one embodiment of the present application is shown, and the figure numerals are as follows: ① positive electrode top cover, ② positive electrode ear glue, ③ battery JR; ④ blue glue; ⑤ aluminum shell; ⑥ negative electrode ear glue; ⑦ negative electrode top cover.
[0065] Fig.10 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0066] Fig.11 This is an optical photograph of the positive electrode slurry prepared in Example 1 after being left to stand for 48 hours.
[0067] Fig.12 This is the low temperature power performance test result of the battery prepared in Example 2.
[0068] Fig.13 This is a computed tomography (CT) photograph of the battery prepared in Example 2.
[0069] Fig.14 This is an optical photograph of the positive electrode slurry prepared in Example 1 after being left to stand for 48 hours.
[0070] Fig.15 This is the low temperature power performance test result of the battery prepared in Example 1.
[0071] Fig.16 This is a CT photograph of the battery prepared in Comparative Example 1.
[0072] Fig.17 This is an optical photograph of the positive electrode slurry prepared in Example 2 after being left to stand for 48 hours.
[0073] Fig.18 This is the low temperature power performance test result of the battery prepared in Example 2. DETAILED DESCRIPTION
[0074] Below, the nano lithium iron phosphate material, positive electrode slurry and positive electrode sheet of the present application, the preparation method of the nano lithium iron phosphate material, positive electrode slurry and positive electrode sheet, and the implementation methods of the secondary battery, battery module, battery pack and power device are specifically disclosed with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0075] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0076] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0077] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0078] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0079] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0080] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0081] [Nano lithium iron phosphate material and preparation method]
[0082] In one embodiment of the present application, a nano lithium iron phosphate material is proposed, which includes nano lithium iron phosphate particles, a covalent organic framework and single-walled carbon nanotubes; the nano lithium iron phosphate particles are located in the pores of the covalent organic framework; the single-walled carbon nanotube material is distributed on the skeleton of the covalent organic framework, or filled in the gap between the covalent organic framework and the nano lithium iron phosphate particles.
[0083] Covalent organic framework (COF) is a kind of organic porous crystalline material connected by covalent bonds of light elements (such as C, O, N, B, etc.), a kind of organic porous polymer with periodicity and crystallinity, and belongs to a three-dimensional ordered material. The present invention fixes nano lithium iron phosphate particles in the pores of the covalent organic framework, limiting the agglomeration of the nano lithium iron phosphate particles during the static process. In addition, the present invention also adds single-walled carbon nanotubes to the material, which can make up for the weakness of poor conductivity of the covalent organic framework to a certain extent, reduce the DCR of the material, and ensure the low-temperature power performance of the battery. Furthermore, the covalent organic framework has a large specific surface area and ordered pores, has a strong adsorption effect on gas, can quickly absorb the gas generated by the battery during the formation cycle and storage process, prevent the central pore from collapsing to a certain extent, and enhance the safety of the battery.
[0084] The structure of the nano lithium iron phosphate material provided in this application is as follows Figure 2 shown.
[0085] A covalent organic framework with a suitable pore size can be selected according to the size of the nano lithium iron phosphate particles. The maximum pore diameter of the covalent organic framework needs to be larger than the nano lithium iron phosphate particle size. In some embodiments, the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.1 (e.g., 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09 or 1:1.1); preferably 1:1.05. When the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.1, the nano lithium iron phosphate particles are more likely to enter the pores, which can alleviate the gelation. At the same time, it is ensured that during the stirring process, the nano lithium iron phosphate particles entering the pores are not easy to come out, avoiding the nano lithium iron phosphate particles from frequently entering and exiting the pores, which is not conducive to being restricted by the covalent organic framework, and thus can better alleviate the gelation effect.
[0086] The smaller the particle size of nano lithium iron phosphate particles, the easier it is to agglomerate. The present application can solve the agglomeration problem of nano lithium iron phosphate particles with small particle size. In some embodiments, the particle size (D50) of the nano lithium iron phosphate particles is less than 100 nm, for example, 1 nm to 10 nm, 10 nm to 20 nm, 20 nm to 30 nm, 30 nm to 40 nm, 40 nm to 50 nm, 50 nm to 60 nm, 60 nm to 70 nm, 70 nm to 80 nm, 80 nm to 90 nm, or 90 nm to 99 nm, for example, less than 70 nm.
[0087] Considering that the performance of single-walled carbon nanotubes is better than that of multi-walled carbon nanotubes, the present application selects single-walled carbon nanotubes to enhance the conductivity of the material and play the role of a partial conductive agent.
[0088] It is generally believed that the smaller the diameter of a single-walled carbon nanotube, the better its conductivity. In some embodiments, the diameter of the single-walled carbon nanotube is 0.7 nm to 1 nm (eg, 0.7 nm, 0.8 nm, 0.9 nm, or 1.0 nm).
[0089] In some embodiments, the length of the single-walled carbon nanotubes selected in the present application is 10 μm to 30 μm (e.g., 10 μm to 15 μm, 15 μm to 20 μm, 20 μm to 25 μm, or 25 μm to 30 μm). Selecting single-walled carbon nanotubes with a length of 10 μm to 30 μm is more conducive to dispersing and interpenetrating the pores of the covalent organic framework and nano-lithium iron phosphate during the stirring process.
[0090] Single-walled carbon nanotubes with high specific surface area can better absorb the gas generated by the battery and reduce the internal pressure of the battery. Therefore, in some embodiments, the specific surface area of the single-walled carbon nanotube is 1000m 2 / g~2000m 2 / g (e.g. 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g or 2000m 2 / g).
[0091] There are many covalent organic frameworks (COFs) that can be used in the present invention. Commercial products can be purchased from the market, or they can be synthesized according to methods described in the literature. In some embodiments, the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 In some embodiments, the covalent organic framework is TFPPY-PYTTA COF (abbreviated as TY-PF COF), and its structural formula and exemplary synthesis route are as follows: Figure 1 As shown, the pore diameter is 70 nm.
[0092] The ratio of each component can be adjusted to better achieve that the nano lithium iron phosphate material does not gel during the static process, while ensuring the power performance of the battery core. In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93% to 96% (for example, 94%): 0.6% to 2% (for example, 0.8% or 1%): 0.1% to 1% (for example, 0.8%). In some embodiments, the content of nano lithium iron phosphate particles is 93%, 94%, 95% or 96% by mass. In some embodiments, the content of covalent organic framework is 0.6%, 0.7%, 0.8%, 0.9% or 1% by mass. In some embodiments, the content of single-walled carbon nanotubes is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% by mass.
[0093] The nano lithium iron phosphate material provided in the present application can be used as a positive electrode active material for secondary batteries, and can also be used in other fields where nano lithium iron phosphate powder is used.
[0094] The second aspect of the present application provides a method for preparing a nano lithium iron phosphate material, comprising the following steps:
[0095] (1) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles;
[0096] (2) adding single-walled carbon nanotubes to the material of step (1) and stirring and mixing to obtain the nano lithium iron phosphate material.
[0097] In the above method, nano-lithium iron phosphate and the covalent organic framework are mixed first, which can make the nano-lithium iron phosphate particles with small particle size fully enter the ordered channels in the covalent organic framework, and prevent the pore size of the ordered channels from becoming smaller due to the addition of single-walled carbon nanotubes first, which makes it impossible for the nano-lithium iron phosphate particles to fully enter the ordered channels of the covalent organic framework.
[0098] In some embodiments, the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.1 (e.g., 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09 or 1:1.1, e.g., 1:1.05).
[0099] In some embodiments, the particle size (D50) of the nano lithium iron phosphate particles is less than or equal to 100nm, for example, 1nm to 10nm, 10nm to 20nm, 20nm to 30nm, 30nm to 40nm, 40nm to 50nm, 50nm to 60nm, 60nm to 70nm, 70nm to 80nm, 80nm to 90nm or 90nm to 99nm, for example, less than 70nm. In some embodiments, the diameter of the single-walled carbon nanotube is 0.7nm to 1nm (for example, 0.7nm, 0.8nm, 0.9nm or 1.0nm). In some embodiments, the length of the single-walled carbon nanotube is 10μm to 30μm (for example, 10μm to 15μm, 15μm to 20μm, 20μm to 25μm or 25μm to 30μm). In some embodiments, the specific surface area of the single-walled carbon nanotube is 1000m 2 / g~2000m 2 / g (e.g. 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m2 / g、1800m 2 / g、1900m 2 / g or 2000m 2 / g).
[0100] In some embodiments, the single-walled carbon nanotubes may be added in the form of slurry. The single-walled carbon nanotube slurry may be commercially available, and the solid content of the single-walled carbon nanotubes in the slurry may be 5% to 10% (eg, 6%).
[0101] In some embodiments, the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF.
[0102] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93-96 (for example, 94): 0.6-2 (for example, 0.8 or 1): 0.1-1 (for example, 0.8) for example (93, 94, 95 or 96): (0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2): (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0).
[0103] In some embodiments, the method is carried out in a stirring tank, and in step (1), the rotational speed of the stirring tank is 20 rpm to 30 rpm (e.g., 25 rpm), and the rotational speed is 700 rpm to 900 rpm (e.g., 800 rpm); in step (2), the rotational speed of the stirring tank is 20 rpm to 30 rpm (e.g., 25 rpm), and the rotational speed is 1000 rpm to 1500 rpm (e.g., 1200 rpm). Such a rotational speed can make the components in the slurry evenly dispersed, so that the slurry maintains appropriate viscosity and fluidity, which is conducive to coating.
[0104] In some embodiments, the stirring time of step (1) or (2) is 0.5 h to 2 h (eg, 0.5 h).
[0105] In some embodiments, the nano-lithium iron phosphate material prepared by the method is the nano-lithium iron phosphate material provided in the first aspect of the present application.
[0106] [Positive electrode slurry and preparation method]
[0107] The third aspect of the present application provides a positive electrode slurry, comprising the nano lithium iron phosphate material of the first aspect of the present application, or the nano lithium iron phosphate material prepared by the method of the second aspect of the present application. Optionally, the positive electrode slurry further comprises one or more of a conductive agent, a binder and an organic solvent.
[0108] As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, the binder is PVDF.
[0109] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, the conductive agent is carbon black (eg, conductive carbon black SP).
[0110] As an example, the organic solvent may be N-methylpyrrolidone (NMP).
[0111] The ratio of each component in the positive electrode slurry can be adjusted to better prevent the slurry from gelling during the static process while ensuring the power performance of the battery cell.
[0112] In some embodiments, the positive electrode slurry includes the nano lithium iron phosphate material, a conductive agent, a binder, and an organic solvent.
[0113] In some embodiments, the ratio of the mass of the binder: (the sum of the masses of the nano-lithium iron phosphate material, the conductive agent and the binder) is 1.5%:100% to 2.5%:100%, for example, 1.5%:100%, 1.6%:100%, 1.7%:100%, 1.8%:100%, 1.9%:100%, 2.0%:100%, 2.1%:100%, 2.2%:100%, 2.3%:100%, 2.4%:100% or 2.5%:100%.
[0114] In some embodiments, the ratio of the mass of the conductive agent to (the sum of the mass of the nano-lithium iron phosphate material, the conductive agent and the binder) is 2%:100% to 4%:100%, for example, 2.0%:100%, 2.1%:100%, 2.2%:100%, 2.3%:100%, 2.4%:100%, 2.5%:100%, 2.6%:100%, 2.7%:100%, 2.8%:100%, 2.9%:100%, 3.0%:100%, 3.1%:100%, 3.2%:100%, 3.3%:100%, 3.4%:100%, 3.5%:100%, 3.6%:100%, 3.7%:100%, 3.8%:100%, 3.9%:100%, 3.1 ... 2.7%: 100%, 2.8%: 100%, 2.9%: 100%, 3.0%: 100%, 3.1%: 100%, 3.2%: 100%, 3.3%: 100%, 3.4%: 100%, 3.5%: 100%, 3.6%: 100%, 3.7%: 100%, 3.8%: 100%, 3.9%: 100% or 4.0%: 100%.
[0115] In some embodiments, the mass ratio of the organic solvent to the mass ratio of the positive electrode slurry is 40%: 100% to 50%: 100% (e.g., 40%: 100%, 41%: 100%, 42%: 100%, 43%: 100%, 44%: 100%, 45%: 100%, 46%: 100%, 47%: 100%, 48%: 100%, 49%: 100%, or 50%: 100%).
[0116] In some embodiments, in terms of mass percentage, the mass ratio of (the sum of the mass of nano lithium iron phosphate material, conductive agent and binder): positive electrode slurry is 50%:100% to 60%:100%, for example, 50%:100%, 51%:100%, 52%:100%, 53%:100%, 54%:100%, 55%:100%, 56%:100%, 57%:100%, 58%:100%, 59%:100% or 60%:100%.
[0117] A fourth aspect of the present application provides a method for preparing a positive electrode slurry, comprising the following steps:
[0118] (i) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles;
[0119] (ii) adding single-walled carbon nanotubes, a binder, a conductive agent and an organic solvent to the material of step (i) and stirring and mixing.
[0120] In the method for preparing positive electrode slurry provided in the present application, the order of adding the materials is: first adding nano lithium iron phosphate and covalent organic framework materials, and then adding single-walled carbon nanotubes, conductive agents, binders and organic solvents, etc. The nano lithium iron phosphate and the covalent organic framework are mixed first, so that the nano lithium iron phosphate with small particle size can fully enter the ordered pores in the covalent organic framework, and the pore size of the ordered pores is prevented from being reduced due to the addition of single-walled carbon nanotubes first, so that the nano lithium iron phosphate particles cannot fully enter the ordered pores of the covalent organic framework.
[0121] In some embodiments, the ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.1 (e.g., 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09 or 1:1.1, e.g., 1:1.05).
[0122] In some embodiments, the particle size (D50) of the nano lithium iron phosphate particles is less than or equal to 100nm, for example, 1nm to 10nm, 10nm to 20nm, 20nm to 30nm, 30nm to 40nm, 40nm to 50nm, 50nm to 60nm, 60nm to 70nm, 70nm to 80nm, 80nm to 90nm or 90nm to 99nm, for example, less than 70nm. In some embodiments, the diameter of the single-walled carbon nanotube is 0.7nm to 1nm (for example, 0.7nm, 0.8nm, 0.9nm or 1.0nm). In some embodiments, the length of the single-walled carbon nanotube is 10μm to 30μm (for example, 10 to 15μm, 15 to 20μm, 20 to 25μm or 25 to 30μm). In some embodiments, the specific surface area of the single-walled carbon nanotube is 1000m 2 / g~2000m 2 / g (e.g. 1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g or 2000m 2 / g).
[0123] In some embodiments, the single-walled carbon nanotubes may be added in the form of slurry. The single-walled carbon nanotube slurry may be purchased from commercial sources, wherein the solid content of the single-walled carbon nanotubes may be 5% to 10% (eg, 6%).
[0124] In some embodiments, the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF.
[0125] As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, the binder is PVDF.
[0126] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, the conductive agent is carbon black (eg, conductive carbon black SP).
[0127] The ratio of each component in the positive electrode slurry can be adjusted to better prevent the slurry from gelling during the static process while ensuring the power performance of the battery cell.
[0128] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93-96 (e.g. 94): 0.6-2 (e.g. 0.8 or 1): 0.1-1 (e.g. 0.8), for example (93, 94, 95 or 96): (0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2): (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0).
[0129] In some embodiments, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes: binder: conductive agent is 93-96 (e.g., 94): 0.6-2 (e.g., 0.8 or 1): 0.1-1 (e.g., 0.8): 1.5-2.5 (e.g., 2.2): 2-4 (e.g., 2.2), for example (93, 94, 95 or 96): (0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1. 3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2): (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0): (1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5): (2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.0).
[0130] In some embodiments, the ratio of the mass of the organic solvent to (the sum of the masses of the nano-lithium iron phosphate particles, the covalent organic framework, the single-walled carbon nanotubes, the conductive agent and the binder) is 40:100 to 50:100, for example, 40:100, 41:100, 42:100, 43:100, 44:100, 45:100, 46:100, 47:100, 48:100, 49:100 or 50:100, in parts by mass.
[0131] In some embodiments, the method comprises the following steps:
[0132] (1) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles;
[0133] (2) adding a binder and a conductive agent to the material of step (1) and stirring and mixing;
[0134] (3) adding an organic solvent to the material of step (2) and stirring and mixing;
[0135] (4) adding single-walled carbon nanotubes to the material in step (3) and stirring and mixing;
[0136] (5) Continuously stirring, adjusting the viscosity to 7000 Pa·s to 15000 Pa·s, and continuing to stir to obtain the positive electrode slurry.
[0137] In some embodiments, the method is carried out in a stirred tank, and in steps (1), (2), and (3), the rotational speed of the stirred tank is 20 rpm to 30 rpm (e.g., 25 rpm), and the rotational speed is 700 rpm to 900 rpm (e.g., 800 rpm); in step (4), the rotational speed of the stirred tank is 20 rpm to 30 rpm (e.g., 25 rpm), and the rotational speed is 1000 rpm to 1500 rpm (e.g., 1200 rpm).
[0138] In some embodiments, step (5) includes: first continuously stirring at an orbital speed of 25 rpm to 30 rpm and a rotational speed of 500 rpm to 600 rpm, adjusting the viscosity within the range of 7000 Pa·s-15000 Pa·s by adding a solvent (such as NMP), and continuously slowly stirring at an orbital speed of 10 rpm to 20 rpm to obtain a positive electrode slurry containing nano lithium iron phosphate material.
[0139] In some embodiments, the stirring time of each step is 0.5 h to 2 h (eg, 0.5 h).
[0140] [Positive electrode sheet and preparation method]
[0141] The fifth aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector; the positive electrode film layer comprises the nano lithium iron phosphate material of the first aspect of the present application, or comprises the nano lithium iron phosphate material prepared by the method of the second aspect of the present application. Optionally, the positive electrode film layer further comprises a conductive agent and a binder.
[0142] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0143] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0144] In the positive electrode film layer, the nano lithium iron phosphate material of the first aspect of the present application, or the nano lithium iron phosphate material prepared by the method of the second aspect of the present application is used as the positive electrode active material. At the same time, the single-walled carbon nanotubes in the nano lithium iron phosphate material also act as a conductive agent.
[0145] In some embodiments, the positive electrode film layer may further include other conventional materials that can be used as positive electrode active materials for batteries. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Positive electrode active materials with suitable particle sizes can be selected as needed to avoid gel problems.
[0146] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, the binder is PVDF.
[0147] In some embodiments, the positive electrode film layer may also optionally include a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the conductive agent is carbon black (e.g., conductive carbon black SP).
[0148] In some embodiments, the positive electrode film layer comprises the nano lithium iron phosphate material of the first aspect of the present application, or comprises the nano lithium iron phosphate material prepared by the method of the second aspect of the present application; the positive electrode film layer further comprises a conductive agent and a binder.
[0149] The ratio of each component in the positive electrode film layer can be adjusted to optimize the power performance of the battery cell. In some embodiments, the binder accounts for 1.5% to 2.5% of the positive electrode film layer by mass percentage (for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%). In some embodiments, the conductive agent accounts for 2% to 4% of the positive electrode film layer by mass percentage (for example, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4.0%).
[0150] The sixth aspect of the present application provides a method for preparing a positive electrode sheet, comprising the following steps: coating the positive electrode slurry of the third aspect of the present application or the positive electrode slurry prepared by the method of the fourth aspect of the present application on a positive electrode collector, and obtaining a positive electrode sheet after cold pressing, slitting and other processes.
[0151] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0152] [Secondary battery]
[0153] In one embodiment of the present application, a secondary battery is provided.
[0154] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0155] [Negative electrode]
[0156] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0157] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0158] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0159] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0160] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0161] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0162] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0163] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after cold pressing, slitting and other processes, the negative electrode sheet can be obtained.
[0164] [Electrolytes]
[0165] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0166] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0167] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0168] In some embodiments, the solvent can be selected from one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0169] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0170] [Isolation film]
[0171] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0172] In some embodiments, the material of the isolation membrane can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0173] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0174] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0175] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0176] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.
[0177] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0178] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0179] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0180] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0181] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0182] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0183] Figure 8 is a secondary battery of cylindrical structure as an example. In some embodiments, referring to Fig. 9 The cylindrical secondary battery includes: ① positive electrode top cover, ② positive electrode ear glue, ③ battery JR; ④ blue glue; ⑤ aluminum shell; ⑥ negative electrode ear glue; ⑦ negative electrode top cover.
[0184] In addition, the present application also provides an electrical device, which includes one or more of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.
[0185] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0186] Fig.10 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0187] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0188] Example
[0189] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0190] Example 1 Preparation of Nano-lithium Iron Phosphate Material and Positive Electrode Slurry
[0191] 1. Synthesis of TY-PF COF
[0192] according to Figure 1 The TY-PF COF was synthesized by the following route:
[0193] (1) Weigh 116.6 mg PyTTA and 123.6 mg TFPPy respectively into a 20 mL Pyrex tube, add 2.7 mL of a mixed solution of mesitylene / dioxane / N,N-dimethylhexamide (10:10:7), sonicate for 10 min to disperse evenly, and quickly add 0.2 mL of 6 M acetic acid aqueous solution. Connect the reaction tube to a vacuum line, freeze it in a liquid nitrogen bath, evacuate it, and flame-seal it after the vacuum pressure indicator stabilizes.
[0194] (2) After the reaction tube was thawed at room temperature, it was placed in a constant temperature oven at 140°C for reaction for 72 hours. After the reaction was terminated, the substance was transferred to room temperature for cooling, filtered, and the upper solid was washed three times with DMF and chloroform in sequence. The product was extracted with chloroform for 72 hours to obtain TY-PF COF, whose pore size was 70 nm.
[0195] 2. Preparation of positive electrode slurry containing nano lithium iron phosphate material
[0196] (1) The covalent organic framework material TY-PF COF and nano lithium iron phosphate powder (commercially available, the particle size of nano lithium iron phosphate particles is less than 70 nm) are mixed in a 5L stirring tank; the above materials are stirred in the stirring tank at a revolution speed of 25 rpm and a rotation speed of 800 rpm for 30 minutes to fully mix them. The nano lithium iron phosphate particles account for 94% of the solid content of the slurry, and the TY-PFCOF accounts for 0.8% of the solid content of the slurry.
[0197] (2) Add PVDF and SP to the above dry mixed materials, and stir at the same speed for 15 minutes. PVDF accounts for 2.2% of the solid content of the slurry, and SP accounts for 2.2% of the solid content of the slurry.
[0198] (3) Add NMP to the dry mixed material to make the solid content of the slurry 55%. Stir for 1 hour to mix the above materials.
[0199] (4) Add CNT slurry (Jiangsu Tiannai, 6% solid content, tube diameter of 0.7nm-1nm, length of 10μm-30μm, specific surface area of 1000m 2 / g~2000m 2 / g), the mass of CNT accounts for 0.8% of the solid content of the slurry. Stirring is performed at a revolution speed of 25 rpm and a rotation speed of 1200 rpm for 30 minutes to uniformly mix the CNT, the covalent organic framework and the nano-lithium iron phosphate.
[0200] (5) Stirring continuously at an orbital speed of 25 rpm and an autorotational speed of 500 rpm, adjusting the viscosity within the range of 7000 Pa·s-15000 Pa·s by adding NMP, and continuing to slowly stir at an orbital speed of 10 rpm to obtain a positive electrode slurry containing nano lithium iron phosphate material.
[0201] The structural diagram of the prepared nano lithium iron phosphate material is shown in Figure 2 , including: covalent organic framework materials (structures such as Figure 1 As shown, the covalent organic framework material has ordered pores; nano-lithium iron phosphate particles are distributed in the ordered pores of the covalent organic framework; carbon nanotubes are distributed on the skeleton of the covalent organic framework material or filled in the gaps between the covalent organic framework material and the nano-lithium iron phosphate particles, connecting the molecules of each material in series.
[0202] The state of the prepared positive electrode slurry after standing for 48 hours is shown in Fig.11 As can be seen from the photos, the slurry prepared in this embodiment still maintains good fluidity after standing for 48 hours, and no slurry gel occurs.
[0203] Example 2 Preparation of positive electrode sheet and secondary battery
[0204] 1. Preparation of positive electrode sheet
[0205] The nano lithium iron phosphate slurry prepared in Example 1 was prepared at a rate of 0.150 g / 1540.25 mm 2 The surface density of the electrode is coated on 13u aluminum foil, and the positive electrode sheet is obtained through cold pressing, slitting and other processes.
[0206] 2. Preparation of negative electrode sheet
[0207] Artificial graphite, SP, CMC, and SBR were mixed according to a certain ratio (95%, 3%, 0.8%, and 1.2%), and fully stirred at a revolution speed of 50 rpm and a rotation speed of 1600 rpm until the mixture was uniform, and the viscosity was adjusted to 6000-12000 Pa·s to obtain a negative electrode slurry.
[0208] The negative electrode slurry was prepared according to 0.8g / 1540.25mm 2 The surface density of the electrode is coated on the 6u copper foil, and the negative electrode sheet is produced through cold pressing, slitting and other processes.
[0209] 3. Preparation of secondary batteries
[0210] The positive electrode sheet and the negative electrode sheet are assembled into a secondary battery together with an electrolyte and an isolating film, wherein the electrolyte contains a solvent (a mixture of EC (ethylene carbonate), DMC (dimethyl carbonate) and EMC (ethyl methyl carbonate)), an additive (VC9 (vinyl carbonate), FEC (French ethylene carbonate), VEC (vinyl ethylene carbonate)) and a lithium salt, and the isolating film uses a 16u PP bare mold. The pole pieces are assembled into cylindrical batteries through processes such as winding, flattening, current collecting plate welding, and top cover welding.
[0211] The low temperature power performance of the battery was tested, and the results are as follows: Fig.12 As shown in the figure, in the battery -20℃ low temperature power test, the lowest voltage is 2.643V.
[0212] Fig.13 This is a CT photo of the cylindrical battery prepared in this embodiment. It can be seen from the photo that the cylindrical battery has no central hole collapse.
[0213] Comparative Example 1
[0214] The positive electrode slurry and cylindrical battery were prepared according to the method of Examples 1 and 2, with other conditions being the same, except that no covalent organic framework material was added to the positive electrode slurry.
[0215] Fig.14 This is an optical photograph of the positive electrode slurry prepared in Comparative Example 1 after standing for 48 hours. It can be seen from the photograph that the slurry has severe gelation and almost no fluidity after standing for 48 hours. Compared with the positive electrode slurry prepared in Example 1, the gelation is significantly deteriorated. The results show that the addition of covalent organic framework materials can significantly improve the gelation phenomenon of the slurry.
[0216] Fig.15 The results of the low temperature power performance test of the battery are shown in the figure. As can be seen from the figure, in the low temperature power test of the battery at -20°C, the lowest voltage is 2.64V, which is not much different from the low temperature power performance of the battery prepared in Example 2, indicating that the addition of the covalent organic framework has no significant effect on the low temperature power performance of the battery.
[0217] Fig.16 This is a CT photo of a cylindrical battery. From the photo, it can be seen that the center hole of the battery has collapsed significantly. The results show that adding porous organic framework materials can improve the stability of the center hole strength of the battery to a certain extent, and can improve the stability of the battery.
[0218] Comparative Example 2
[0219] The positive electrode slurry and cylindrical battery were prepared according to the method of Examples 1 and 2, with other conditions being the same, except that no single-walled carbon nanotubes were added to the positive electrode slurry.
[0220] Fig.17 This is an optical photograph of the positive electrode slurry prepared in Comparative Example 2 after standing for 48 hours. It can be seen from the photograph that the slurry has no obvious gel after standing for 48 hours and still maintains good fluidity, indicating that the addition of single-walled carbon nanotubes has no obvious effect on improving the slurry gel.
[0221] Fig.18 The figure shows the low-temperature power performance test results of the battery. It can be seen from the figure that in the -20°C low-temperature power test of the battery, the lowest voltage is 2.56V. Compared with the battery prepared in Example 2, the low-temperature power performance is deteriorated by 80mV, indicating that adding single-walled carbon nanotubes can reduce the DCR of the battery and significantly improve the low-temperature power performance of the battery.
[0222] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A nano lithium iron phosphate material, comprising nano lithium iron phosphate particles, a covalent organic framework and single-walled carbon nanotubes; the nano lithium iron phosphate particles are located in the pores of the covalent organic framework; the single-walled carbon nanotube material is distributed on the skeleton of the covalent organic framework, or filled in the gap between the covalent organic framework and the nano lithium iron phosphate particles; The ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.
1.
2. The nano lithium iron phosphate material according to claim 1, wherein: The particle size of the nano lithium iron phosphate particles is less than or equal to 100 nm.
3. The nano lithium iron phosphate material according to claim 1, wherein: The single-walled carbon nanotube has a diameter of 0.7 nm to 1 nm, a length of 10 μm to 30 μm, and / or a specific surface area of 1000 m 2 / g~2000m 2 / g.
4. The nano lithium iron phosphate material according to claim 1, wherein: The covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF, and / or In terms of mass percentage, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotube is 93% to 96%: 0.6% to 2%: 0.1% to 1%.
5. A method for preparing nano lithium iron phosphate material, comprising the following steps: (1) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles; (2) adding single-walled carbon nanotubes to the material of step (1) and stirring to obtain the nano lithium iron phosphate material; The ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.
1. 6 . The method according to claim 5 , wherein the particle size of the nano lithium iron phosphate particles is less than or equal to 100 nm.
7. The method according to claim 5, wherein the single-walled carbon nanotube has a diameter of 0.7 nm to 1 nm, a length of 10 μm to 30 μm, and / or a specific surface area of 1000 m 2 / g~2000m 2 / g.
8. The method according to claim 5, wherein the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PY COF, COF-5, SP 2 One or more of C-COF, PY-AN COF; and / or Calculated by weight, the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotube is 93-96: 0.6-2: 0.1-1.
9. The method according to any one of claims 5 to 8, wherein the method is carried out in a stirring tank, wherein in step (1), the rotational speed of the stirring tank is 20 rpm to 30 rpm, and the rotational speed is 700 rpm to 900 rpm; and in step (2), the rotational speed of the stirring tank is 20 rpm to 30 rpm, and the rotational speed is 1000 rpm to 1500 rpm.
10. A positive electrode slurry, comprising the nano lithium iron phosphate material according to any one of claims 1 to 4, or comprising the nano lithium iron phosphate material prepared by the method according to any one of claims 5 to 9. 11 . The positive electrode slurry according to claim 10 , further comprising one or more of a conductive agent, a binder and an organic solvent. 12 . The positive electrode slurry according to claim 11 , comprising the nano lithium iron phosphate material, a conductive agent, a binder and an organic solvent.
13. The positive electrode slurry according to claim 12, wherein the ratio of the mass of the binder to (the sum of the mass of the nano-lithium iron phosphate material, the conductive agent and the binder) is 1.5%:100% to 2.5%:100% in terms of mass percentage.
14. The positive electrode slurry according to claim 12, wherein the ratio of the mass of the conductive agent to (the sum of the mass of the nano-lithium iron phosphate material, the conductive agent and the binder) is 2%:100% to 4%:100% in terms of mass percentage. 15 . The positive electrode slurry according to claim 12 , wherein the ratio of the mass of the organic solvent to the mass of the positive electrode slurry is 40%:100% to 50%:100% by mass.
16. The positive electrode slurry according to claim 12, wherein the mass ratio of (the sum of the mass of the nano lithium iron phosphate material, the conductive agent and the binder): the mass ratio of the positive electrode slurry is 50%:100% to 60%:100%.
17. A method for preparing a positive electrode slurry, comprising the following steps: (i) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles; (ii) adding single-walled carbon nanotubes, a binder, a conductive agent and an organic solvent to the material of step (i) and stirring and mixing; The ratio of the diameter of the nano lithium iron phosphate particles to the pore diameter of the covalent organic framework is 1:1.0 to 1:1.
1.
18. The method according to claim 17, wherein the particle size of the nano lithium iron phosphate particles is less than or equal to 100 nm.
19. The method according to claim 17, wherein the single-walled carbon nanotube has a diameter of 0.7 nm to 1 nm, a length of 10 μm to 30 μm, and / or a specific surface area of 1000 m 2 / g~2000m 2 / g.
20. The method according to claim 17, wherein the covalent organic framework is selected from TFPPY-PYTTA COF, TF-PYCOF, COF-5, SP 2 One or more of C-COF, PY-AN COF.
21. The method according to claim 17, wherein the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes is 93-96: 0.6-2: 0.1-1 in mass fractions.
22. The method according to claim 17, wherein the ratio of nano lithium iron phosphate particles: covalent organic framework: single-walled carbon nanotubes: binder: conductive agent is 93-96: 0.6-2: 0.1-1: 1.5-2.5: 2-4 in mass fractions.
23. The method according to claim 17, wherein the ratio of the mass of the organic solvent to the mass of the nano-lithium iron phosphate particles, the covalent organic framework, the single-walled carbon nanotubes, the conductive agent and the binder is 40:100 to 50:
100.
24. The method according to any one of claims 17 to 23, comprising the steps of: (1) stirring and mixing the covalent organic framework and nano-lithium iron phosphate particles; (2) adding a binder and a conductive agent to the material of step (1) and stirring and mixing; (3) adding an organic solvent to the material of step (2) and stirring and mixing; (4) adding single-walled carbon nanotubes to the material in step (3) and stirring and mixing; (5) Continuously stirring, adjusting the viscosity to 7000 Pa·s to 15000 Pa·s, and continuing to stir to obtain the positive electrode slurry.
25. The method according to claim 24 is carried out in a stirring tank, wherein in steps (1), (2) and (3), the rotational speed of the stirring tank is 20 rpm to 30 rpm, and the rotational speed is 700 rpm to 900 rpm; in step (4), the rotational speed of the stirring tank is 20 rpm to 30 rpm, and the rotational speed is 1000 rpm to 1500 rpm.
26. The method according to claim 24, wherein step (5) comprises: First, the mixture is stirred continuously at an orbital speed of 25 rpm to 30 rpm and a rotational speed of 500 rpm to 600 rpm, the viscosity is adjusted to be within the range of 7000 Pa·s-15000 Pa·s by adding a solvent, and the mixture is stirred slowly continuously at an orbital speed of 10 rpm to 20 rpm to obtain a positive electrode slurry containing nano lithium iron phosphate material.
27. A positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer comprises the nano lithium iron phosphate material according to any one of claims 1-4, or comprises the nano lithium iron phosphate material prepared by the method according to any one of claims 5-9. 28 . The positive electrode sheet according to claim 27 , wherein the positive electrode film layer further comprises a conductive agent and a binder.
29. The positive electrode plate according to claim 28, wherein, by mass percentage, the binder accounts for 1.5% to 2.5% of the positive electrode film layer, and / or the conductive agent accounts for 2% to 4% of the positive electrode film layer.
30. A method for preparing a positive electrode sheet, comprising the following steps: The positive electrode slurry according to any one of claims 10 to 16 or the positive electrode slurry prepared by the method according to any one of claims 17 to 26 is coated on a positive electrode current collector, and after cold pressing and slitting, a positive electrode sheet is obtained.
31. A secondary battery, comprising the nano lithium iron phosphate material according to any one of claims 1-4, the nano lithium iron phosphate material prepared by the method according to any one of claims 5-9, the positive electrode sheet according to any one of claims 27-29, or the positive electrode sheet prepared by the method according to claim 30.
32. A battery module, comprising the nano lithium iron phosphate material according to any one of claims 1-4, the nano lithium iron phosphate material obtained by the method according to any one of claims 5-9, the positive electrode sheet according to any one of claims 27-29, the positive electrode sheet obtained by the method according to claim 30, or the secondary battery according to claim 31.
33. A battery pack, comprising the nano lithium iron phosphate material according to any one of claims 1-4, the nano lithium iron phosphate material obtained by the method according to any one of claims 5-9, the positive electrode sheet according to any one of claims 27-29, the positive electrode sheet obtained by the method according to claim 30, the secondary battery according to claim 31, or the battery module according to claim 32.
34. An electrical device, comprising the nano lithium iron phosphate material according to any one of claims 1-4, the nano lithium iron phosphate material obtained by the method according to any one of claims 5-9, the positive electrode sheet according to any one of claims 27-29, the positive electrode sheet obtained by the method according to claim 30, the secondary battery according to claim 31, the battery module according to claim 32, or the battery pack according to claim 33.
Citation Information
Patent Citations
Compound lithium iron phosphate material and preparing method thereof, positive electrode piece and lithium ion battery
CN108288699A
Positive pole material of lithium ion battery, preparation method of positive pole material and lithium ion battery
CN109524658A
Silicon carbon anode material and preparation method thereof
CN110416500A